Kualitas Pelayanan Pembuatan Kartu Keluarga Di Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Donggala - Nampa, Usman (Jurnal ADMINISTRATOR, 2025)
This research is a qualitative research using a Phenomenology approach. This study aims to determine the family card making service at the Office of Population and Civil Registration of Donggala Regency. Data collection and analysis were carried out through the process of observation, interviews and documentation by having important and relevant information to the problem. The theory used in this paper is the theory of service quality proposed by Taliziduhu Ndaraha (2003), which explains that there are four indicators used to measure the level of public satisfaction, namely: Physical Evidence (Tangibles), Reliability, Responsiveness and Assurance. The results of this study indicate that the Family Card Making Service system at the Office of Population and Civil Registration of Donggala Regency, public administration services at the office are quite good, but there are some shortcomings that need to be fixed, namely the lack of facilities and infrastructure and the lack of public awareness of the importance of family cards